Characteristics of sleep–wake cycle and sleep duration in Japanese type 2 diabetes patients with visceral fat accumulation. Issue 1 (31st March 2017) - Fukuda, Shiro; Hirata, Ayumu; Nishizawa, Hitoshi; Nagao, Hirofumi; Kimura, Takekazu; Fujishima, Yuya; Yamaoka, Masaya; Kozawa, Junji; Imagawa, Akihisa; Funahashi, Tohru; Maeda, Norikazu; Shimomura, Iichiro
Abstract : Later bedtime and shorter estimated sleep duration existed in the T2DM patients with visceral fat accumulation, compared to those without. Abstract: Sleep pattern has been shown to be associated with type 2 diabetes mellitus. Here, we investigated the difference in bedtime, waking time and estimated sleep duration in type 2 diabetes mellitus patients with or without visceral fat accumulation, using a questionnaire on sleep patterns. The study participants were 59 Japanese type 2 diabetes mellitus patients (men/women 34/25, age 64.5 ± 12.1 years). Visceral fat accumulation was defined as estimated visceral fat area ≥100 cm 2 . The patients with visceral fat accumulation ( n = 40) showed significantly later bedtime (23.51 ± 01.27 h in the [+] group vs 22.49 ± 01.23 h in the [−] group) and shorter estimated sleep duration (6.6 ± 1.4 h in the [+] group vs 7.9 ± 1.0 h in the [−] group) on weekdays, compared with those without ( n = 19). Later bedtime and shorter estimated sleep duration existed in the type 2 diabetes mellitus patients with visceral fat accumulation, compared with those without.